Moderating Role of Psychological Ownership between Authentic Leadership and Sports Team Performance: Mediating Effect of Sports Training - Dr. Mohanad Mohammed Sufyan Ghaleb; Dr. Arsalan Mujahid Ghouri , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study examines the mediating influence of sports training between authentic leadership (AL) and sports team performance (STP) in the setting of Saudi Arabia, with the moderating role of psychological ownership (PO). This study employs a cross-sectional survey design to obtain data from 300 members of sports teams. The results indicate that AL significantly and positively affects STP and that sports training mainly mediates this relationship. In addition, the data indicate that PO moderates the relationship between AL and athletic performance, such that the association is stronger for team members with a strong feeling of PO. These findings have significant implications for Saudi Arabian organizations seeking to improve the performance of their sports teams. While adopting the study's conclusions, it is recommended that employers engage in AL development, give frequent athletic training chances, promote a sense of Unity among team members, and consider cultural and socioeconomic aspects. We examine the study's limitations and potential areas for future investigation.